La terre et le béton : le projet d’urbanisme considéré sous l’angle du métabolisme territorial - Mathieu Fernandez; Corinne Blanquart; Éric Verdeil (VertigO)
This paper proposes an alternative approach about a stock quantification of matter mobilized by an urban planning project, aiming at improving urban metabolism. Actually, territorial metabolism studies reveal that urbanization processes generate the main mart of material flows produced by territories, in direct extraction or garbage production. The objective of the paper is to present a method permitting to quantify matter flows resulting from the realization of an urban planning project whose privileged form in France is the ZAC – ie concerted planning zone –, considering the time scale of its implementation and its perimeter. Quantification methods are based on data available only at administrative scales – region, department or communes –, exceeding largely urban projects scale. The field analyzed for this paper is an urban renewal project in the Grand Paris metropolis, in Vitry-sur-Seine. Considering ground and built artifacts in the quantification process, the originality of the method consists in producing results concerning masses of earth and concrete mobilized by the project. Then, the results show the centrality of these matters for circular economy politics based, for example, on an increasing circularity of matter in urban environment.